Thresholds of income inequality that mitigate the role of gender inclusive education in promoting gender economic inclusion in Sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This study provides thresholds of inequality that should not be exceeded if gender inclusive education is to enhance gender inclusive formal economic participation in sub-Saharan Africa. The empirical evidence is based on the Generalised Method of Moments and data from 42 countries during the period 2004-2014. The following findings are established. First, inclusive tertiary education unconditionally promotes gender economic inclusion while the interaction between tertiary education and inequality is unfavourable to gender economic inclusion. Second, a Gini coefficient that nullifies the positive incidence of inclusive tertiary education on female labour force participation is 0.562. Second, the Gini coefficient and the Palma ratio that crowd-out the negative unconditional effects of inclusive tertiary education on female unemployment are 0.547 and 6.118, respectively. Third, a 0.578 Gini coefficient, a 0.680 Atkinson index and a 6.557 Palma ratio are critical masses that wipe-out the positive unconditional effects of inclusive tertiary education on female employment. Findings associated with lower levels of education are not significant. As the main policy implication, income inequality should not be tolerated above the established thresholds in order for gender inclusive education to promote gender inclusive formal economic participation. Other implications are discussed in the light of Sustainable Development Goals. This research complements the existing literature by providing inequality thresholds that should not be exceeded in order for gender inclusive education to promote the involvement of women in the formal economic sector.
Keywords: G20; I10; I32; O40; O55; 330; Africa; Inequality; Gender; Inclusive development